CORRELATION OF CONCEPT OF AMA AND FREE RADICAL THEORY - Ranjan, Rohit; Srivastava, Sanjay (International Journal of Ayurveda and Pharma Research, 2015)
Majority of the endogenous disease begins with the formation of Ama in the body. It has tremendous capacity to vitiate the Doshas and disturbing the homeostasis (Dhatu-samya). Ama is the resultant of improper digestion or partially digestion of the food particle due to hypofunction of Jatharagni and also due to accumulation of mala in the body and also considered as Prathamdoshadusti. It may be considered as partially or incompletely metabolized Dhatu in case of Dhatvagnimandya. In modern parameters, Ama is supposed to be deadly Free radical. Free radical is an atom/molecule that contains one or more unpaired electron, which requires neutralization by free radical scavengers. Ama is not a single entity but is a generalized term, which can be applied to many malformed substances in the body. This Ama is responsible for the production of various diseases. In the same way, free radicals are also found to be the root cause of many diseases. Here we discuss about properties and qualities in both entities, which are similar and dissimilar, also whether free radicals can be considered under Ama. The present article attempts to correlate the most recent concept of todays i. e. free radical concept with that of the concept of Ama, described in research for remedies from Ayurvedic research, which may be helpful in the presentation and care of free radicals mediated disease.